Social and cultural anthropology: the key concepts - Rapport, Nigel (Routledge key guides, 2014)
"Social and Cultural Anthropology: the Key Concepts is an easy to use A-Z guide to the central concepts that students are likely to encounter in this field.Now fully updated, this third edition includes entries on:Material CultureEnvironmentHuman RightsHybridityAlterityCosmopolitanismEthnographyApplied AnthropologyGenderCyberneticsWith full cross-referencing and revised further reading to point students towards the latest writings in Social and Cultural Anthropology, this is a superb reference resource for anyone studying or teaching in this area. "--